Unsaying the said: Emmanuel Levinas and the Zhuangzi on linguistic scepticism. Issue 1 (1st June 2019) - Berenpas, Martine
In this article I compare the linguistic skepticism of Levinas to that of the early Daoist skepticism of the Zhuangzi. I will argue that both Levinas as the Zhuangzi use skepticism as a therapeutic tool to question the rigid use of language and to create an openness in the self in which the self is inspired by something more than itself. For Levinas, language is primarily a response-ability; language ultimately refers to the absolute responsibility to the Other. For the Zhuangzi, words are simply too rigid to attune to the subtle differences and changes in the world. Through carefree wandering, the self becomes more receptive to the unfolding of the way (Dao).Both the Zhuangzi as Levinas see language not only as a system of references that is able to convey the world, but also see language as communication; as a response to the outside world. For Levinas, this response-ability is aimed at the Other and is primarily an ethical demand. For the Zhuangzi, genuine language is more a spontaneous receptivity; a wandering with words in which words are open to different interpretations and perspectives. In the end of this article I will argue that Levinas and the Zhuangzi see language as a communicative praxis that mirrors receptivity and passivity.